Formação continuada para coordenadores pedagógicos: e a escola, como fica? - Garcia, Marilene (2008)
This study talks over the continuing formation program specifically on the understanding of the pedagogical practice of the pedagogic coordinator in the school. The objective was to know if the knowledge distributed in the continuing formation program from 2001 to 2004 attended by pedagogic coordinators of the local government schools got to the schools, to understand the reasons the knowledge got or did not get there, and to understand how the socialization of the knowledge happens. It has been recorded as being fundamental for the development of the work, the participation of four professionals working as pedagogic coordinators in elementary education public schools of São Paulo City. The participants were chosen as follows: two professionals who work at schools with recommendation of good performance , two professionals who work at schools with indication of low performance . Individual and recurrent interviews were used as the procedure to data collection. The obtained data were grouped taking as reference the pedagogic coordinator duty, the continuing formation courses and the different ways of socializing knowledge with the teachers. Each of these groupings gave rise to the categories of analysis based on some concepts and principles of the developmental theories of Henri Wallon and Lev. S. Vygotsky. According to the pedagogic coordinators reports, the results had the following conclusions: the knowledge acquired from the continuing formation courses, between 2001 and 2004, was partly shared in the school by the pedagogic coordinators, and therefore there was not specific impact of the actions during this period in the school practice. The reasons why the knowledge was not brought into effect were mainly lack of follow-up by the administration, lack of running the actions, a lot of formation actions at the same time, formation actions that did not take into consideration the professionals needs